IDENTIFYING DOMINANT RISK AND ANALYSING ITS IMPACT TO FINANCIAL VIABILITY IN WATER SUPPLY CONCESSION SCHEME - HUSNULLAH PANGERAN (NIM : 25003004); Pembimbing : DR. Ir. Krishna S. Pribadi; DR. Ir. Purnomo , MOCH.
This research identifies the most influencing risk factors in water supply concession scheme and develops a risk analysis model to describe its impact to investment financial viability, based on PBP, NPV and IRR criteria. A survey was conducted to government, private sector and independent boards respondent to identify dominant risk factors. The dominant risk factors are determined based on rank of total score of each factor using maximum likelihood method. The risk analysis model used a stochastic approach based on montecarlo simulation technique, applied to cashflow model assumed under uncertain condition, with three concession scenarios, i.e. full concession, intake-water treatment plant concession, and transmission-distribution concession. The survey result shows that there are five risk factors percepted by respondent as the dominant or most influencing, and possibly taken by the private sector, namely tariff changes, non revenue water (NRW), exchange rate, water demand, and operation cost-overrun. The simulation and sensitivity analysis result indicate that tariff changes as a risk factor has the most significant influence to investment financial viability, followed by NRW, water demand, exchange rate, and operation cost-overrun. Both methods (survey and simulation analysis) provided a coherent result in the ranking of all five risk factors, except for exchange rate and water demand which differ slightly in ranks. In addition, the use of stochastic model in risk analysis offers more information about the possible outcome of investment, which provide the decision maker with different views for considering the investment proposal. Unlike the deterministic analysis, developed in this research using a capital asset pricing model (CAPM) for discount rate selection, which shows that the transmission-distribution concession is not feasible, the stochastic model shows that there is a possibility for the investor that the transmission-distribution concession become feasible, as shown by the positive value of the NPV.